Comparative Analysis of Deflections and Crack Opening Widths in Reinforced Concrete Whole Beams Under the Action of Single, Low-Cycle Repetitive and Low-Cycle Alternating Loads - Masjuk, Grigory; Yushchuk, Oleksandr; Masjuk, Wladislav; Semko, Pavlo (International Journal of Engineering and Technology, 2018)
Article contains a comparative analysis of the deflections and the crack opening widths in the reinforced concrete whole beams affected by single, low-cycle repeated and short-cycle alternating loads according to experimental data. Experimental studies have shown that the stress-strained state of the whole beams affected by low-cycle repeated and short-cycle alternating loads significantly differs from the stress-strained state of the same beams affected by nonalternating static loads.Following parameters of the stress-strained state were determined: crack resistance and deformability, crack opening widths and deflections have considerably higher values. This is caused to certain extent by the change in the concrete structure after repeated and alternating loads. The concrete structure, affected by alternating loads, changes due to the formation of microcracks, which increase from cycle to cycle, forming the main cross-cutting cracks, dividing the beam by length into separate blocks. Due to this, the beam stiffness decreases and the deflections increase, as well as the crack opening widths.Â Â